Erasmus country ranking: towards quality student mobility - Sobral, Sónia Rolland (2020)
Erasmus is a European Commission program which has been a huge success: more and more higher education students decide to move to one of the 34 countries that belong to the program. This article begins by analysing the reasons behind why students take a semester at another university in another country, and what the motivations for their choices are. The literature review reveals that there are personal, destination and academic reasons. Students who decide to make Erasmus mobility do not know how to choose the higher education institution where they will do said mobility. This article aims to help these students by ranking Erasmus mobility countries following the reasons that are identified in the literature as the most important. To rank Erasmus mobility countries, we use two criteria: destination and academic. The destination was subdivided into 7 items: Adventure, Cultural and Heritage, Safe and Secure, Cost of Living, Geographic Localization, Weather, Language and Sustainable. The academic part was divided into 3 items: research, university quality and sustainable. For each of the items we use the strongest and most reliable indicators. We also compare our ranking with the real number of student mobility for each of the 34 countries.